Between likes and lies: how teenage girls navigate online health information - Seo, Hyunjin; Burkett, K. Macy; Morales, Olga; Izhar, Nazra; Chaif, Rim Hayat; Coelho, Michaella Barros; Ha, Huong; Jona, Blessing; Iqbal, Azhar; Doyle, Taylor (Frontiers in Communication, 2025)
IntroductionThis study examined how high school teenage girls in the United States navigate and evaluate health information on social media, as well as the barriers they face in accessing and interpreting such content.MethodsWe conducted an online survey of high school teenage girls in the United States to understand their social media use and assessment of online health information. Our survey included both open-ended and closed-ended questions, generating qualitative and quantitative data on the research topics. A quota sampling approach was used to ensure the survey sample was representative of the population in terms of race, ethnicity, and geographic location.ResultsOur findings highlight three key challenges teenage girls face in navigating health information online: information overload, conflicting messages, and risks associated with misinformation. This research also shows that factors such as self-efficacy, self-esteem, and household socioeconomic status influence teenage girls’ social media use and digital information competence, which in turn affect how they access online health misinformation.DiscussionThis study fills an important gap in research by providing empirical insights into how teenage girls evaluate beauty and health information on social media. It contributes to health communication studies by showing how digital health information environments both reinforce and complicate longstanding gendered dynamics related to health, idealized body standards, and equitable access to information. This research also offers practical implications for enhancing digital health literacy among teenage girls through targeted programs and informed guidance for educators, policymakers, and caregivers.